SNP (Single Nucleotide Polymorphism) at Adiponectin Gene in Type 2 Diabetes Mellitus (T2DM) Patients - TYAS NYONITA PUNJUNGSARI (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2023)
SNPs haplotype blocks can be used as genetic markers to trace particular diseases (means indirectly tracks the causative genes). One of the SNPs that affect disease is SNP positions 45 and 276. SNPs 45 and 276 in the APMI or ADIPOQ or Adiponectin that affect insulin production on T2DM patients. The aim of this research was to identify the presence of SNP 45 in patients with type 2 diabetes mellitus. Method of this research is descriptive exploration using type 2 diabetes mellitus patients in Gledug Village, Blitar Regency as specimen donors. Identification using DNA extraction, DNA Amplification, sequencing and bioinformatics analysis. The results of this project seven DNA extracted, the seven sequences have the same Qv20+ value as the sequence base pair, alignment analysis using blast, when compared with the adipoQ gene sequence with accession number NG_021140.1, it was found that the KT, SR and BP sequences had a 100% similarity level. Identification of candidate SNPs in the absence of the adenine nucleotide was found in the SR, KT, and ST sequences